2000
DOI: 10.1007/pl00013765
|View full text |Cite
|
Sign up to set email alerts
|

Rotational acetabular osteotomy for severely dysplastic acetabulum

Abstract: The operative procedures chosen for arthrosis with severe acetabular dysplasia vary among orthopaedic surgeons. We operated on 250 hips using the rotational acetabular osteotomy (RAO) method of Ninomiya and Tagawa [8]. In this report, we describe the technique of RAO and the results of this procedure in patients with severely dysplastic hips. Among the 250 hips, there were 6 which were classified as Severin group V. In those hips, the CE angle was less than 0 degrees, and the femoral head showed superolateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 10 publications
1
24
1
Order By: Relevance
“…Furthermore, the efficacy of this procedure has also been shown in patients with severe dysplasia of the hip at an early stage (Takatori et al 1996, Nozawa et al 2000, Clohisy et al 2005. We found that RAO was not effective in maintaining the preoperative osteoarthritic stage in patients with a severely deformed femoral head, even in early osteoarthritis of the hip.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, the efficacy of this procedure has also been shown in patients with severe dysplasia of the hip at an early stage (Takatori et al 1996, Nozawa et al 2000, Clohisy et al 2005. We found that RAO was not effective in maintaining the preoperative osteoarthritic stage in patients with a severely deformed femoral head, even in early osteoarthritis of the hip.…”
Section: Discussionmentioning
confidence: 57%
“…Steel's triple osteotomy (Steel 1973), Wagner's spherical acetabular osteotomy (Wagner 1976), the rotational acetabular osteotomy (RAO) developed by Ninomiya and Tagawa (1984), and Ganz periacetabular osteotomy (Ganz et al 1988) allow the femoral head to be covered with articular cartilage and have been used successfully in patients with developmental dysplasia of the hip and no or early osteoarthritic involvement (Nakamura et al 1998b, Schramm et al 1999, Siebenrock et al 1999, Nozawa et al 2000, Takatori et al 2001). Acetabular dysplasia is common in the general population in Europe (Jacobsen et al 2005).…”
mentioning
confidence: 99%
“…Untreated severe dysplasia of the hip frequently leads to OA, and periacetabular osteotomy usually is the preferred treatment for young patients with severe dysplasia [4,25] and deformity of the femoral head [5]. Our data suggest anteroposterior radiographs of the hip in the standing position should be obtained when evaluating the preoperative stage of OA to determine the indications for periacetabular osteotomy in patients with dysplasia.…”
Section: Discussionmentioning
confidence: 81%
“…Satisfactory long-term results of periacetabular osteotomy for residual dysplasia after open reduction have been reported [18,20,25,26]. Satisfactory middle-or long-term clinical and radiographic results of periacetabular osteotomy also have been reported for patients with severe dysplasia [2,19,26]. In contrast, unsatisfactory long-term radiographic results of periacetabular osteotomy have been reported for patients with severe deformity of the femoral head, particularly those with early osteoarthritis of the hip [21].…”
Section: Discussionmentioning
confidence: 99%